Advances in immunotherapy for melanoma management - Dany, Mohammed (Hum Vaccin Immunother, 2016)
Melanoma remains a leading cause of death among young adults. Evidence that melanoma tumor cells are highly immunogenic and a better understanding of T-cell immune checkpoints have changed the therapeutic approach to advanced melanoma. Instead of targeting the tumor directly, immunotherapy targets and activates the immune response using checkpoint inhibitors, monoclonal antibodies, vaccines, and adoptive T cell therapy. This review focuses on the immune signaling and biological mechanisms of action of recent immune-based melanoma therapies as well as their clinical benefits.